2017
DOI: 10.3389/fpls.2017.01985
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling and Physiological Responses of Halophyte Kochia sieversiana Provide Insights into Salt Tolerance

Abstract: Halophytes are remarkable plants that can tolerate extremely high-salinity conditions, and have different salinity tolerance mechanisms from those of glycophytic plants. In this work, we investigated the mechanisms of salinity tolerance of an extreme halophyte, Kochia sieversiana (Pall.) C. A. M, using RNA sequencing and physiological tests. The results showed that moderate salinity stimulated the growth and water uptake of K. sieversiana and, even under 480-mM salinity condition, K. sieversiana maintained an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Comparative transcriptome analyses have previously been reported for a few halophytes, such as Halogeton glomeratus ( Yao et al, 2018 ; Wang et al, 2015 ), Iris lactea var. chinensis ( Gu et al, 2018 ), Kochia sieversiana ( Zhao et al, 2017 ), Nitraria sibirica Pall. ( Li et al, 2017a ), Suaeda maritima ( Gharat et al, 2016 ), Sporobolus virginicus ( Yamamoto et al, 2015 ), and Mesembryanthemum crystallinum ( Oh et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative transcriptome analyses have previously been reported for a few halophytes, such as Halogeton glomeratus ( Yao et al, 2018 ; Wang et al, 2015 ), Iris lactea var. chinensis ( Gu et al, 2018 ), Kochia sieversiana ( Zhao et al, 2017 ), Nitraria sibirica Pall. ( Li et al, 2017a ), Suaeda maritima ( Gharat et al, 2016 ), Sporobolus virginicus ( Yamamoto et al, 2015 ), and Mesembryanthemum crystallinum ( Oh et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kochia sieversiana can subsist at high salinity, most AQP genes were significantly up-regulated in 419 low, but not high salinity stressed roots (Zhao et al, 2017). In contrast, the halophyte Schrenkiella 420 parvula expressed a high number of AQPs for tolerance to salt toxicity with TIP2 being highly 421 expressed in S. parvula root as compared to shoot tissues (Loqué et al, 2005;Oh et al, 2014).…”
Section: Growth and Ion Balance Under Agricultural Effluent Water 412mentioning
confidence: 97%
“…AlHKT2;1 transcript level was found to be upregulated in the shoot at 12 and 24 h, while significant transcript abundance was recorded during K + starvation in the roots (Sanadhya et al 2015). Zhao et al (2017) reported the four HKT gene members in a halophytic grass Kochia sieversiana, where no significant transcript abundance was observed for HKT genes under the salt stress (Zhao et al 2017).…”
Section: 2mentioning
confidence: 99%
“…The major non-enzymatic action consists of ascorbate, glutathione, carotenoids, and tocopherol antioxidants (Nikalje et al 2017). There are many reports available on the characterization of halophyte antioxidant enzymes and their roles in ROS scavenging (Muchate et al 2016;Zhao et al 2017). In Sesuvium portulacastrum, physio-biochemical analysis of a facultative halophyte was maintained with the help of antioxidant enzyme activity (CAT, GR, SOD, APX, and GPX) under the salt stress (Muchate et al 2016).…”
Section: Production and Maintenance Of Reactive Oxygen And Nitrogen Smentioning
confidence: 99%
See 1 more Smart Citation